1996
DOI: 10.1121/1.417460
|View full text |Cite
|
Sign up to set email alerts
|

Palato-lingual contact patterns during voiced and unvoiced consonant production

Abstract: The timing of the initiation and cessation of vocal fold vibrations characterizes the voiced and unvoiced stops. The results of perceptual experiments, however, have revealed that other cues, such as the duration of preceding vowels, the patterns of the formant transitions in the following vowels, and the period of stop closures, may play important roles in differentiating these cognates. Therefore, the present study is to further investigate the role of the tongue articulatory movements during voiced and unvo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Duration of the burst: Slis and Cohen (1969) reported that the noise burst duration of Dutch plosives was on average 15 ms shorter for voiced plosives than for voiceless plosives. The difference in burst duration may be explained by the spatially more extended contact at constriction for voiceless plosives in comparison to voiced plosives (e.g., Cho & Ladefoged, 1999;Yoshioka, Murase, & Uematsu, 1996). Ernestus (2000) measured burst durations of 649 Dutch plosives in medial position and showed that expert listeners tended to classify plosives with short bursts durations as voiced and plosives with long burst durations as voiceless.…”
Section: Measurement Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Duration of the burst: Slis and Cohen (1969) reported that the noise burst duration of Dutch plosives was on average 15 ms shorter for voiced plosives than for voiceless plosives. The difference in burst duration may be explained by the spatially more extended contact at constriction for voiceless plosives in comparison to voiced plosives (e.g., Cho & Ladefoged, 1999;Yoshioka, Murase, & Uematsu, 1996). Ernestus (2000) measured burst durations of 649 Dutch plosives in medial position and showed that expert listeners tended to classify plosives with short bursts durations as voiced and plosives with long burst durations as voiceless.…”
Section: Measurement Proceduresmentioning
confidence: 99%
“…Power of the burst above 500 Hz: Slis and Cohen (1969) found that the amplitude of the voiceless noise burst was about 50% higher than the amplitude of the voiced noise burst. Possible causes for this difference mentioned in the literature are higher oral pressure behind the constriction and/or spatially more extended closure for voiceless plosives (e.g., Yoshioka et al, 1996). The burst (as described under 2) was first high-pass filtered at a cutoff frequency of 500 Hz.…”
Section: Measurement Proceduresmentioning
confidence: 99%
“…, 자음산출 시 조음 기관의 운동역학적 측면 (Yoshioka et al, 1996;Higashikawa et al, 2003), 음도나 말소리에 대한 지각 (Higashikawa et al, 1996;Ito et al, 2005;Vestergaard et al, 2007), 혹은 성대의 해부생리적 특성 (Rubin et al, 2006;Sundberg et al, 2010…”
unclassified